Cardiomyocyte FGF signaling is required for Cx43 phosphorylation and cardiac gap junction maintenance - Sakurai, Takashi (2013)
Cardiac remodeling resulting from impairment of myocardial integrity leads to heart failure, through still incompletely understood mechanisms. The fibroblast growth factor (FGF) system has been implicated in tissue maintenance, but its role in the adult heart is not well defined. We hypothesized that the FGF system plays a role in the maintenance of cardiac homeostasis, and the impairment of cardiomyocyte FGF signaling leads to pathological cardiac remodeling. We showed that FGF signaling is required for connexin 43 (Cx43) localization at cell–cell contacts in isolated cardiomyocytes and COS7 cells. Lack of FGF signaling led to decreased Cx43 phosphorylation at serines 325/328/330 (S325/328/330), sites known to be important for assembly of gap junctions. Cx43 instability induced by FGF inhibition was restored by the Cx43 S325/328/330 phospho-mimetic mutant, suggesting FGF-dependent phosphorylation of these sites. Consistent with these in vitro findings, cardiomyocyte-specific inhibition of FGF signaling in adult mice demonstrated mislocalization of Cx43 at intercalated discs, whereas localization of N-cadherin and desmoplakin was not affected. This led to premature death resulting from impaired cardiac remodeling. We conclude that cardiomyocyte FGF signaling is essential for cardiomyocyte homeostasis through phosphorylation of Cx43 at S325/328/330 residues which are important for the maintenance of gap junction.